Multi-netclust: an efficient tool for finding connected clusters in multi-parametric networks - Kuzniar, Arnold (Oxford University Press, 2010)
Summary: Multi-netclust is a simple tool that allows users to extract connected clusters of data represented by different networks given in the form of matrices. The tool uses user-defined threshold values to combine the matrices, and uses a straightforward, memory-efficient graph algorithm to find clusters that are connected in all or in either of the networks. The tool is written in C/C++ and is available either as a form-based or as a command-line-based program running on Linux platforms. The algorithm is fast, processing a network of > 10(6) nodes and 10(8) edges takes only a few minutes on an ordinary computer. Availability: http://www.bioinformatics.nl/netclust/ Contact: jack.leunissen@wur.nl Supplementary information: Supplementary data are available at Bioinformatics online.